Novel nuclear technology for controlled production of n-type semiconductor - Sutjipto, Agus Geter Edy; Yahya, Ruslan; Muhida, Riza (2010)
Use of semiconductors for power electronics requires unique material characteristics because of the high power levels flowing in the devices. In this research, NTD silicon was try to be developed by using Cf-252 isotopic neutron radioactive sourced (1.6 mCi) instead of using neutron source from nuclear reactor. It was found that concentration of P between 0.5 and 14 wt% could be produced by irradiating silicon using netron between 1 and 5 days. It was proved that the irradiation time did not change the mechanical property of the material.